On the Outside Looking In: A Global Doula Response to COVID-19 - Searcy, Julie Johnson; Castañeda, Angela N. (Frontiers in Sociology, 2021)
From around the world, doulas report the impact of new COVID-19 restrictions on their ability to provide continuous emotional, physical, and informational support to pregnant people and their families. In a qualitative survey conducted in March and April 2020, we heard from over 500 doulas in 24 countries. Doulas practicing across the world revealed rapid changes to hospital policies. Even accounting for different public health responses across countries, the doulas in our study pointed to one common theme - their absence at births and the subsequent need to support birthing people virtually. In a follow-up survey and in interviews we conducted in July, we reconnected with doulas from our initial study to track their access to institutional birthing spaces. As countries experienced the effects of “flattening the curve,” we found that doulas were still not considered “essential” workers and the majority could not attend births. Our research shows that doulas have ambiguous feelings about the efficacy of virtual support, that they raise concerns about the long-term impact of COVID on their profession and that they are concerned about mistreatment and obstetric violence as birthing people enter hospitals alone.